Lightning trip-out risk assessment and differential lightning protection of 35 kV transmission lines in mountain wind farm - Ying Yang (Elsevier, 2022)
Lightning trip out of collecting line has become a serious threat to the safe and reliable operation of mountain wind farm. It is urgent to carry out lightning trip out risk assessment and differential protection of 35kV collecting line of mountain wind farm. In this paper, considering the mountain terrain, tower structure, insulation configuration, grounding resistance and other factors, an accurate calculation model of lightning trip out rate is established, and the lightning trip out distribution law of each tower in wind farm is obtained. In this paper, the lightning trip risk of collector lines is classified according to the improved analytic hierarchy process of ”base-by-base tower – tower section – whole line”. Finally, considering the economy of wind farm lightning protection, three kinds of wind farm collector line differential protection schemes are proposed. The results show that the lightning trip-out risk assessment of the line I and line II of a wind farm is carried out by using the improved chromatography analysis method. The lightning trip rates of the line I and line II are 2.299 times/100 km⋅a and 1.740 times/100 km⋅a, respectively. This shows that the wind farm’s circuit is faced with serious lightning trip risk. Considering the effect of lightning protection and economy of lightning protection, scheme 2 is adopted to carry out the lightning protection transformation of line I and line II. The risk of lightning trip out of line I and line II is reduced by 55% and 62.7% respectively, and the technical economy of lightning protection of scheme 2 is the best. Therefore, it is suggested to adopt scheme 2 as the lightning protection transformation measure of the collection line of the wind farm. The above research can provide technical reference for lightning protection of wind farm collector lines in the future.